Limiting rise in heat load with an ice vest during elite female rugby sevens warm-ups - Henderson, M. J.; Chrismas, B. C. R.; Stevens, C. J.; Fransen, J.; Coutts, A. J.; Taylor, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To determine the effect of wearing a phase-change cooling vest in elite female rugby sevens athletes during (1) a simulated match-day warm-up in hot conditions prior to a training session and (2) a prematch warm-up during a tournament in cool conditions.